Conduction treatment of temporal lobe epilepsy in rats: the dose-effect relationship between current resistance and therapeutic effect - Zhang, Shaohui; Yuan, Liu; Liu, Chunxiu; Kuang, Suhui; Wang, Jiaqi; Liang, Shuli; Cong, Ming (Frontiers in Neurology, 2023)
Objective To investigate the effect of current resistance on therapeutic outcomes, and the mechanism of current conduction treatment in a rat model of temporal lobe epilepsy (TLE). Methods Rats were randomly divided into four groups: normal control, epileptic group, low-resistance conduction (LRC) and high-resistance conduction (HRC) group. The content of glutamate (Glu) and gamma-amino butyric acid (GABA) in the hippocampus was determined using a neurotransmitter analyzer. mRNA and protein expression of interleukin 1β (IL-1β) /IL-1 receptor 1(IL-1R1) and high mobility group protein B1 (HMGB-1)/toll-like receptor-4 (TLR-4) in hippocampal neurons were tested. Video electroencephalogram monitoring was used to record seizures and EEG discharges. Cognitive function in the rats was tested using the Morris water maze. Results Glu/GABA ratio in the epileptic control and HRC groups was significant differences from LRC group. The levels of HMGB1/TLR4 and IL-1β/IL-1R1 in the LRC group and normal control group were significantly lower than those in epileptic control group (p < 0.01) and the HRC group. The mRNA levels of HMGB1/TLR4 and IL-1β/IL-1R1 in the LRC group and normal control group were significantly lower than those in epileptic control group. The frequency of total and propagated seizures was lower in the LRC group than in the epileptic control and HRC groups (p < 0.01). The numbers of platform crossings in the LRC group and normal control group were significantly higher than those in the epileptic control and HRC groups in the space exploration experiment. Conclusion Current resistance affected seizure control and cognitive protection in rats with TLE treated by current conduction. The lower current resistance, the better seizure control and cognitive protection in rats with TLE treated by current conduction. Glu/GABA, IL-1β/IL-1R1, and HMGB1/TLR-4 may participate in the anti-seizure mechanism of current conduction treatment.